Hybrid mesoporous nanorods with deeply grooved lateral faces toward cytosolic drug delivery. (16th October 2019) - Sun, Kaiyao; Ding, Tao; Xing, Yuxin; Mo, Dong; Zhang, Jixi; Rosenholm, Jessica M.
Abstract : Hybrid mesoporous nanorods with six twisted sharp edges can induce effective penetration of intracellular barriers and cytosolic delivery of membrane-impermeable drugs through curvature effects. Abstract : Nanocarriers with high local curvatures hold a great potential of inducing effective penetration of intracellular barriers and cytosolic delivery of membrane-impermeable drugs. However, the fine control of the sharp edges and their morphological effects inside cells remains largely unexplored. Herein, a nanocarrier system of hybrid mesoporous nanorods with six-arm star-shaped end faces and groove-patterned lateral faces was developed to maximize surface regions with high local curvatures for enhancing membrane destabilization. Specifically, twisted (right-handed) nanorods (TNR, diameter ∼120, aspect ratio 4–5) with a hexagon cross-section from a templated synthesis were modified by amino groups to promote surface coating of a wet-adhesive polymer, i.e. polydopamine (PDA). An edge-preferential deposition of PDA by local curvature effects led to the protective etching of silica, and in turn, the formation of nanorods with varying groove depths at different volumes of the aqueous coating solution. Finally, branched polyethylene imine (PEI) was grafted on the exterior surface of the nanorods for enhancing the dispersity and cellular uptake rate. As verified by elaborate in vitro investigations, the configuration of nanorods with the sharpest edges/deepest grooves can be rotated to a lying-down/upright mode in order to minimize/maximize the membrane tension during the interaction with membranes, which consequently resulted in highly efficient lysosomal escape despite the relatively lower uptake degree. The successful delivery of vorinostat (SAHA, a FDA-approved histone deacetylase inhibitor) and inhibition of cancer cells demonstrated the attractive ability of the nanocarriers in drug delivery.